Examining the influence of e-Health in motivating cervical cancer screening and HPV vaccination among college students - Khan, Tazrin Jannat (Kansas State University, 2018)
Background: Cervical cancer is one of the leading lethal diseases diagnosed in women globally. By early diagnosis and vaccine, cervical cancer can be prevented. Young adults are mainly at risk of cancer-causing HPV. But they are not motivated to take HPV vaccine and screening test. It is crucial to communicate young adults by education and information about cancer. Electronic health (e-Health) communication strategy has the potential to raise awareness about cancer prevention and control. This study examined the key motivational determinants that are associated with college student’s cervical cancer and HPV prevention behavior in relation to their online health information seeking behavior. Method: An online survey among college students (n= 405), age range 18- 35 years was conducted. All measures were from validated instruments and modified to examine the current study’s objectives structured with key variables derived from the Protection-Motivation theory (PMT). Data from the survey were analyzed statistically using Statistical Package for the Social Sciences (SPSS) software. The reliability of the scales used was assessed through the calculation of coefficient alpha and the dimensionality of the scale was tested through confirmatory factor analysis using the principal components method of extraction. Descriptive of the study variables, Pearson correlation coefficient, One-way ANOVA, and multiple linear regression analysis were done to test the research questions and hypothesis. Results: Result showed that, perceived vulnerability to HPV (β= .17, t= 4.53, p= .000), self-efficacy (β= .13, t= 2.91, p< .01), and response costs (β= .46, t= 10.44, p= .000) were the key motivational variables that are associated with college student’s HPV vaccine and Pap test. In testing predictors for online health information seeking behavior, perceived response-efficacy (β= .20, t= 3.41, p= .001) and response costs (β= .19, t= 3.21, p= .001) gained significance in the model. Also, a Pearson correlation coefficient showed a positive association between college student’s online health information seeking behavior and motivation for preventive measures (r = .10, p = .05). Result demonstrated that, college student’s knowledge about HPV and cervical cancer influenced their motivation for HPV vaccine and Pap test (p< .001) but knowledge did not influence their online health information seeking behavior (p= .43). Conclusion: E-Health strategy can be an effective tool for targeting young adults and should be explored further in cancer communication and vaccine promotion. It is important for cancer communication interventions to promote e-Health strategy and enhance the usage of online health information seeking behavior. The contents of online health education and information need to be upgraded to provide the maximum benefits to the public.
Keywords: Cervical cancer; College students; MotivationE-Health